Simultaneous analysis of major ingredients of Gardenia fruit by HPLC-MS/TQMS method - Galaqin, M; Uwai, K; Yuguchi, M; Iwasa, T (Mongolian Journal of Chemistry, 2017)
An efficient, accurate HPLC-MS/TQMS method was introduced for the quantitative/qualitative simultaneous analysis of main ingredients, namely geniposide and genipingentiobioside, in the Gardenia fruit. The separation was successfully obtained using a C8 (100mm×2.1mm, 5μm, 30°C) column by gradient elution with ultrapure water as mobile phase, where flow rate was set to 0.2 ml/min and detection wavelength at 240 nm. The analytical method was validated and the quantification of active compounds, namely genipingentiobioside and gardenoside, was performed. Linearity, precision, repeatability, stability and recovery were also reported. The quantitative analysis revealed that both main ingredients as geniposide and genipingentiobioside have performed a good linear relationship in 0.1-100 mg/ml concentration range (r=1.00000 and r =0.99998). The average content was measured to be 4.842% with RSD 0.96% for geniposide and 1.1976% with RSD 0.47% for genipingentiobioside in the Gardenia fruit. Accordingly, this method would be feasible for the quantity and quality control of crude drugs.